2010
DOI: 10.2478/v10042-010-0049-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of nasal mucosa, olfactometry and rhinomanometry in patients after CO2 laser mucotomy in inferior turbinate hypertrophy.

Abstract: Abstract:To evaluate the cytology of nasal mucosa and sense of smell and nasal patency in patients underwent carbon dioxide laser turbinoplasty (CO 2 laser mucotomy) due to chronic nasal hypertrophy. 46 patients with inferior turbinate hypertrophy underwent complete laryngological examination, anterior rhinomanometry, olfactory measurements and cytology of nasal mucous which were performed before and 3 months after CO 2 laser mucotomy. Laser mucotomy was performed under local anesthesia. Cytograms revealed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…To date, results have been mixed with a general trend toward better results with radiofrequency and partial resection techniques and worse effects with electrocautery and laser techniques. [30][31][32][33][34][35][36][37][38] A consensus based on these results cannot be reached at this time.…”
Section: Complicationsmentioning
confidence: 99%
“…To date, results have been mixed with a general trend toward better results with radiofrequency and partial resection techniques and worse effects with electrocautery and laser techniques. [30][31][32][33][34][35][36][37][38] A consensus based on these results cannot be reached at this time.…”
Section: Complicationsmentioning
confidence: 99%
“…However, they focused on epithelial cells and did not stratify for different rhinitis types. Olszewska et al [9] evaluated cytological changes after CO 2 laser mucotomy, without reporting data on allergies. They observed a decrease in goblet cell proportion 3 months after the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement or the absence of alterations of epithelial cells in nasal mucosa has been demonstrated with histological and cytological evaluations [6][7][8][9][10]. However, previous studies did not assess inflammatory infiltrate and did not stratify for types of rhinitis, such as allergic and nonallergic rhinitis and cellular subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…However there is some published data on 940 nm diode laser tissue effects, showing that in contrast to carbon dioxide laser (l ¼ 10,600) that causes a superficial vaporization of the tissue with a broad carbonization zone and penetration depth of 0.1 mm, it provides deeper tissue penetration with a rather thin carbonization layer and pronounced coagulation zone up to 1-3 mm as evaluated by means of optical microscopy (hematoxylin and eosin staining) and scanning electron microscopy [25]. Concerning histopathological changes following laser surgery, it could be shown that the lamina propria was occupied by fibrous tissues, and that the number of vessels and seromucinous glands in the turbinates had decreased [26][27][28]. Some authors found that laser assisted turbinate surgery disturbed mucociliary function [29,30], whereas Willat et al [31] found the postoperative mucociliary clearance to be unchanged.…”
Section: Discussionmentioning
confidence: 99%